2018
DOI: 10.1186/s13321-017-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR study of steroidal and azaheterocyclic human aromatase inhibitors using quantitative profile of protein–ligand interactions

Abstract: Aromatase is a member of the cytochrome P450 superfamily responsible for a key step in the biosynthesis of estrogens. As estrogens are involved in the control of important reproduction-related processes, including sexual differentiation and maturation, aromatase is a potential target for endocrine disrupting chemicals as well as breast cancer therapy. In this work, 3D-QSAR combined with quantitative profile of protein–ligand interactions was employed in the identification and characterization of critical steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Two techniques are commonly used for the global application of the predictive modeling in toxicology, for example, employing either a large dataset using techniques such as machine learning methods or deriving mechanistically interpretable simple models [14,15]. Both techniques have been exploited to create predictive models for the antagonist activity of azoles with CYP19A1 [16][17][18][19][20]. Shoombuatong et al, 2018, reviewed this area and concluded that the modeling of nonsteroidal aromatase inhibition requires nitrogen-containing descriptors, polarizability, the energy of highest occupied molecular orbital (HOMO), the energy gap of highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO gap), and descriptors for hydrogen bond acceptors [21].…”
Section: Or 4 Respectively) Present Inmentioning
confidence: 99%
“…Two techniques are commonly used for the global application of the predictive modeling in toxicology, for example, employing either a large dataset using techniques such as machine learning methods or deriving mechanistically interpretable simple models [14,15]. Both techniques have been exploited to create predictive models for the antagonist activity of azoles with CYP19A1 [16][17][18][19][20]. Shoombuatong et al, 2018, reviewed this area and concluded that the modeling of nonsteroidal aromatase inhibition requires nitrogen-containing descriptors, polarizability, the energy of highest occupied molecular orbital (HOMO), the energy gap of highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO gap), and descriptors for hydrogen bond acceptors [21].…”
Section: Or 4 Respectively) Present Inmentioning
confidence: 99%
“…The current trend (2016-2018; Figure 4 (Fig. 4) ) shows that eight articles (Song et al, 2016[ 91 ]; Ghodsi and Hemmateenejad, 2016[ 32 ]; Adhikari et al, 2017[ 1 ]; Prachayasittikul et al, 2017[ 72 ]; Pingaew et al, 2018[ 70 ]; Lee and Barron, 2018[ 49 ]; Barigye et al, 2018[ 9 ]) have already been published in comparison to a total of 13 publications for the previous 5 years. Thus, it is promising that the number of publication regarding AIs utilizing QSAR models for prediction will continue to grow.…”
Section: Qsar Models Of Aromatase Inhibitory Activitymentioning
confidence: 99%
“…The authors noted that these results were further validated with the 3D-QSAR analysis while the HQSAR model inferred the importance of the p -cyanophenyl moiety in regulating AI. Additionally, Lee and Barron (2018[ 49 ]) conducted 3D-QSAR studies on the bioactivity (IC 50 ) of 124 compounds exhibiting AI activity (steroidal and heterocyclic). Multiple linear regress-ion combined with genetic algorithm (GA-MLR) was used to build the models which was then validated via the LOO and external validation methods.…”
Section: Qsar Models Of Aromatase Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…До недавнего времени в связи с отсутствием информации о трехмерной структуре ароматазы новые ингибиторы CYP19A1 разрабатывались с привлечением непрямых методов компьютерного конструирования лекарств, базирующихся на анализе известных лигандов к ферменту и последующем выявлении их общих структурных свойств, которые обусловливают биологическую активность [6][7][8]. Определение методом рентгеноструктурного анализа пространственной структуры ароматазы высокого разрешения [2,9] создало предпосылки не только для понимания функции и механизма действия фермента, но и для разработки новых эффективных ингибиторов CYP19А1 на основе прямых методов компьютерного конструирования лекарств, использующих данные о структуре молекулярной мишени (см., например, работы [10][11][12][13][14][15][16][17][18][19][20][21]).…”
Section: Introductionunclassified